REVISED ARTICLE TITLE: ENHANCING CHEMISTRY SELF-CONCEPT AMONG HIGH SCHOOL STUDENTS IN KENYA THROUGH COMPUTER-BASED SIMULATIONS - Smith , Thomas; Johnson, Maria (Top Educational Review Journal (TERJ), 2024)
Chemistry education is essential in developing a scientific attitude in learners, but the poor performance of secondary school students in the subject has become a concern in Kenya. Factors such as the learners’ chemistry self-concept can contribute to this issue. This study aimed to investigate the effectiveness of computer-based simulations (CBS) as a teaching approach to improve the chemistry self-concept of high school students in Nakuru Sub-county, Kenya. A quasi-experimental research design was used, involving the Solomon Four Non-Equivalent Control Group Design, with a sample size of 175 students. The Chemistry Self-Concept Questionnaire (CSCQ) and a CBS module developed by the researcher were used to collect data. The results showed that students taught through CBS had a significantly higher level of chemistry self-concept than those taught through Regular Teaching Methods (RTM). Furthermore, there was no statistically significant gender difference in self-concept towards Chemistry of students taught through CBS. The findings suggest that using CBS as a teaching approach could be a promising strategy to address the issue of poor performance in Chemistry. With the current impact of the COVID-19 pandemic, the use of computer-based learning has become increasingly important, making the results of this study relevant in this context